Effectivity of lemuru fish oil (sardinella longiceps) protection in periodontal tissue wistar rats induced by diabetes mellitus - Rizka SA. Putri; Dian W. Damaiyanti; Hansen Kurniawan (Journal of Dentomaxillofacial Science, 2022)
Objective: To determine the effect of lemuru fish oil extract (Sardinella longiceps) on the number of fibroblasts in periodontal tissue of Wistar rats induced by diabetes mellitus using streptozotocin. Material and Methods: Thirty-two Wistar rats male, were divided into 4 groups, group K0 (negative control), K1 (4ml/kgBB), K2 (8ml/kgBB), and K3 (4ml/kgBB). Rats were induced with nicotinamide and streptozotocin to create a state of diabetes. The experiment of giving lemuru fish oil extract was carried out for 21 days.The number of fibroblast cells in periodontal tissue with HE staining was performed. The data were analyzed by One-Way ANOVA and Post-Hoc LSD test. Results: The LSD test showed a significant difference between the group without treatment and the group using treatment lemuru fish oil. Group with Lemuru fish oil can increase the number of fibroblasts and the most effective dose is 8ml/kgBB. Conclusion: Lemuru fish oil extract (Sardinella longiceps) can increase the number of fibroblasts in periodontal tissue of Wistar rats induced by diabetes mellitus.